Pengembangan kewirausahaan berbasis teknologi pada Amal Usaha Muhammadiyah dan Aisyiyah di Karanganyar - Wibowo, Frendy; Setiawan, Adi Andika; Ramahdan, Nofia Fajar; Khasanah, Aulia Uswatun (Nur Science Institute, 2024)
This community service aims to develop technology-based entrepreneurial skills in SMK Muhammadiyah 6 Karanganyar students. With the rapid development of technology, digital-based entrepreneurial skills are becoming very relevant and needed in today's world of work. This program is designed to improve students' knowledge of modern entrepreneurship, including using digital technology in marketing, production, and business management. The methods used include entrepreneurship training, the use of technology in business, and direct assistance in student entrepreneurship projects. This activity also involves collaboration with experienced local industry players, allowing students to learn from real practices in the field. The results of the community service show that this training and mentoring program significantly improves students' understanding of the concept and application of technology-based entrepreneurship. Students become more skilled in developing business ideas using digital platforms and social media. In addition, this activity strengthens students' motivation to become entrepreneurs and gives them confidence in facing future challenges. This program is expected to improve the competence of SMK Muhammadiyah 6 Karanganyar graduates, making them more prepared to enter the job market that focuses on technological innovation.